Valores do dinheiro e propensão ao endividamento: uma análise em estudantes de uma instituição federal de ensino superior - Avelar, Lúcio Flávio Trindade (2014)
This study's main objective is to identify the existence of a relationship between the Amounts of Money and Propensity to Indebtedness in students. One of the advantages of this work is to check what the values are assigned to the money and the existence of a relationship between factors of Money Values and Propensity to Indebtedness of college students, as well as identifying factor levels and the Propensity to Indebtedness. The study will be conducted in line with the concepts of behavioral finance, covering topics such as values of cash, debt and related research and is characterized as a descriptive and quantitative research.The population consists of students from areas of knowledge pertaining to the study of social sciences at the Federal University of Maranhão, the courses that make up the Centre for Social Sciences (CCSO) Campus in the City of St. Louis for a total sample of 360 individuals online. As analysis technique for checking the meaning of the Securities Money Factor analysis was used. In verifying the Propensity to Indebtedness the variables that make up the Attitude Scale of the Indebtedness proposed in the work of Moura (2005), Disney and Ganthergood (2011) and Flowers (2012) was used. As a result 10 factors and their respective Cronbach Alphas were found: Conflict (0.900), Pleasure (0.864), Power (0.820), Culture (0.800), Detachment (0.765), inequality (0.733), Concern (0.693), Progress (0.740), stability (0.681) and self-realization (0.620). Regarding the levels of Propensity to Indebtedness was identified that 97.51% have an average score for Propensity to Indebtedness and 2.49% shows a high level of Propensity to Indebtedness. As the association was identified that all factors are associated with the average level of Propensity to Indebtedness and there was a predominance of medium and high levels for most of Values Money factors.